La cooperación económica entre Asia meridional y Latinoamérica, una mirada desde el Sur - Chun Lee, Po (2020)
This work analyzes the period after the Great Recession of 2008, the possibility, and the challenges for South-South economic cooperation between Asia and Latin America, paying special attention to India and South Asia as potential countries to promote development among emerging states. To achieve this purpose, this article uses historical methodology to review data and quantitative facts from primary sources with the intention of highlighting the historical episodes that allow us to interpret the willingness to cooperate between the two regions. Based on the precepts of the New Regionalism, a sustainable and constructive cooperative framework is conceived where the possible scenarios or niches to carry out such cooperation are observed. This paper finds that to increase intra-regional economic cooperation it is necessary to understand the existing cooperation platforms between emerging countries proposed by configurations such as IBSA, BRICS, or institutions such as AIIB, or the BRICS Bank.